The importance of benchmarking in the innovative activities of tourism enterprises: The case study of LOT SA Polish Airlines - Gierczak-Korzeniowska, Beata (Turyzm/Tourism, 2016)
The aim of this article is to identify the importance of benchmarking as a source of innovation in the activities of tourism enterprises through the case study of LOT S.A. Polish Airlines. To expand, the objective was to identify the departments within the company which used benchmarking as a stimulus to create a new or improve an existing offer. The subject was an airline belonging to Star Alliance and 27 employees from selected departments. The study used questionnaires and. with managers of selected departments only, open standardized interviews. Statistical inference methods, including a chi-square test, were applied to analyse the data. Although the introduction of benchmarking in the company's structure allows for a quick escape route from a cycle of limitation in the company’s own culture and standard behaviour (and the acquisition of knowledge during the process gives rise to new and innovative ideas) the importance of this method in innovative activities did not result in any practical application. A lack of knowledge about benchmarking was noticeable, and an identification of this method with a simple competitive analysis resulted in failures in business activity as well as a lack of creativity in its application.